Income Content of the World Coffee Exports (2019)
Coffee is the most widely commercialized tropical product on the international market. The 2009/10 crop had an estimated value of $15.4 billion, with 93.4 million bags exported. According to the International Coffee Organization (ICO, 2011), the coffee sector employed around 26 million people in 56 producing countries and over 100 exporting countries. But how would coffee products rank, in terms of income content, in relation to other commercialized products, and how have they evolved? To answer this question, the annual income content of 5,111 products exported by 167 countries from the period between 2000 and 2009, was calculated. Data from the UNCOMTRADE (2011), and “sophistication” indicators proposed by Hausmann and Rodrik (2003) who classify different products according to their productivity, were used. An emphasis was put on five coffee products (whole grain, roasted, decaffeinated, caffeinated, and soluble), showing the evolution of the number of exporting countries and of the “sophistication” index (income content), whose temporal variation was decomposed by the effects of competitiveness and income per capita changes. The results showed that non-roasted, non-decaffeinated, whole grain coffee is still the most commercialized product, but with the lowest income content of all coffee products, occupying the twenty-fourth worst position in terms of income content in 2009. The roasted, decaffeinated coffee presented the greatest income growth in the period, placing itself in the 3,309th position in 2009. The decomposition of the index showed that for coffee products with the most processing, the greatest cause of export sophistication growth was the Revealed Comparative Advantage effect. Products with the least amount of processing presented a loss in relative market share, with the addition of values to the production chain occurring outside those countries producing the raw materials.